ECONOMIC POLICY INDEPENDENCE IN EU MEMBER STATES: POLITICAL ECONOMY OF CROATIAN MEMBERSHIP (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: The independence of the economic policy of national states in the European Union is a relevant and politically controversial issue as notions of lost sovereignty are often evoked by populist political options. It is therefore important to distinctly outline the actual state of affairs.Methodology: Methodology is descriptive and comparative. The article starts by surveying traditional and recent political, institutional and economic arguments on policy convergence in areas undergoing economic integration. The article continues by contrasting the complex notion of economic sovereignty and the ongoing development of economic policy constrictions of EU (and eurozone) membership. Croatia is then compared to relevant economies in key economic policies in response to the crisis of 2008/09 in order to evaluate the maneuvering room left by the various policy constrictions.Results: Particular attention is devoted to the comparison of exchange rate policy, fiscal policy and monetary policy employed by member states in response to the crisis of 2008/09. While economic independence in terms of crisis management is clearly reduced by virtue of EU and eurozone membership, its effects should not be felt as a change of policy direction in the case of Croatia.Conclusion: We conclude that the policy restrictions imposed by EU membership and expected entry into the eurozone are in line with economic restraints and exhibited national policy preferences prior to EU accession.